Enhancing Family Resilience in Urban Areas Through Inclusive Banking: a Maslahah Mursalah Perspective on BRI Services - Aziz, Abdul (Al-madinah: Journal of Islamic Civilization, 2025)
Inclusive financial services play a crucial role in enhancing family economic resilience, particularly for micro and small business owners. However, challenges remain in utilizing banking services, such as limited financial literacy and access to capital. This study aims to analyze the effectiveness of BRI's financial services in strengthening family resilience through the perspective of maslahah mursalah. This research employs a qualitative approach using a case study method on MSME customers who utilize People's Business Credit (KUR) and BRI's digital services. The study involved eight informants. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that BRI's services significantly contribute to improving family economic stability by providing broader access to capital, enhancing financial literacy, and supporting small business growth. From the perspective of maslahah mursalah, these services fulfill the principles of utility (jalb al-mashalih) and harm prevention (dar’ al-mafasid), although challenges remain in optimizing digital financial inclusion and simplifying administrative processes. The study's implications highlight the importance of increasing financial literacy, optimizing digital services, and fostering collaboration with the government and Islamic financial institutions to sustainably strengthen family economic resilience.